Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1164/ajrccm/148.3.618
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Cardiac Arrhythmias: Is There a Relationship?

Abstract: To determine if there was a relationship between cardiac arrhythmias and sleep apnea, we studied the prevalence of arrhythmias in a consecutive series of patients referred to our clinic for assessment of this disorder. Two hundred of 263 physician-referred patients were eligible for the study and, of these, 173 (86.5%) had complete investigations. All patients underwent a full night of polysomnography and Holter monitoring. Sleep apnea was diagnosed if patients had more than 10 apneas and hypopneas per hour (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
1
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 15 publications
5
90
1
9
Order By: Relevance
“…Comparable results have been reported by FLEMONS et al [26] who showed that prevalence of cardiac arrhythmias was low in apn-oeic patients without serious cardiac or respiratory co-morbidity and was similar to their prevalence in healthy subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Comparable results have been reported by FLEMONS et al [26] who showed that prevalence of cardiac arrhythmias was low in apn-oeic patients without serious cardiac or respiratory co-morbidity and was similar to their prevalence in healthy subjects.…”
Section: Discussionsupporting
confidence: 85%
“…Guilleminault et al [9] reported PVC in 19% patients with sleep apnea (n = 400). Similarly, Flemons and Mehra reported PVCs in 2.6 and 41.5% sleep apnea patients, respectively [10,11]. The latter reported higher prevalence probably because the study was done among elderly population while other studies including ours, predominantly had middle aged men and women with OSA.…”
Section: Discussionsupporting
confidence: 53%
“…The prevalence of atrial fibrillation reported in our study was only 1 in 273 OSA patients, probably secondary to selection bias as our patients were most often referred by physicians for snoring and daytime somnolence rather than by cardiologists. Nevertheless, a lower prevalence of AF in patients with OSA (3-5.3%) has been reported among other studies [9][10][11]. The corollary has not been true though.…”
Section: Discussionmentioning
confidence: 77%
“…40 -42 Moreover, conclusions as to whether arrhythmias are more common among those with SDB are conflicting. 40,42 In some studies, it appears that arrhythmias were more common in SDB patients who had severe nocturnal hypoxemia during REM sleep. 41 A recent study among patients who had undergone successful cardioversion for atrial fibrillation demonstrated an 82% rate of recurrence over a 12-month period in contrast to a 42% and 53% rate of recurrence among OSA patients treated with CPAP and controls who did not undergo a sleep study, respectively.…”
Section: Sleep Disordered Breathing and Cardiac Arrhythmias Epidemiologymentioning
confidence: 99%